ANALISIS RESIKO USAHA TELUR AYAM RAS DI BATURAJA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
Analysis of changes in wetland area and the factors that influence it in South Ogan Komering Ulu Regency.The purpose of this research is to analyze the change of rice field in South Ogan Komering Ulu Regency. Analyzing the factors affecting changes in wetland area in South Ogan Komering Ulu Regency. The method of determining the location of the research and the determination of the respondents was done purposively and carried out from October to December 2017 in South Ogan Komering Ulu Regency.The research method used is literature study method where the research is done with the study of library resources based on data and information that has been done in the form of secondary data. Types and data sources used are secondary data taking into account the availability of data, this study used data during the year (2007-2016). Secondary data were obtained from literature studies, reports, publications, and other literature related to the study, as well as the agencies or agencies involved in the study, such as the Central Bureau of Statistics of OKUS and other relevant agencies. The analytical method used is quantitative analysis and supported by qualitative descriptive analysis. To answer the first purpose used mathematical calculations and to answer the second goal used multiple regression analysis. Based on the result of the research, it is concluded that the change of rice field in South Ogan Komering Ulu Regency decreased from year to year with the decreasing rate of 0,929% per year and the factors that have significant effect on the change of land area are the PDRB of agriculture sector, population, and long way. Keyword: Analysis, changes in wetland area, and change factor of rice field